Cascading failures to attack on edges in interdependent networks. (2018) - Cui, Dan; Shen, Charles; Peña-Mora, Feniosky; Chen, Jianguo
Networks interact with and depend on each other in modern society, operating and functioning as interdependent networks. In this paper, the cascading process of the interdependent networks against the attack on edges is studied. Then the robustness of the heterogeneous coupled networks and homogeneous coupled networks under random attack and targeted attack is fully explored. It is found that for heterogeneous and homogeneous coupled networks, no particular type always performs better than any other. However, in general, homogeneous coupled networks exhibit better robustness than the heterogeneous ones in most cases. It is also found that under targeted attack, no matter what the type of the interdependent network, it gets more vulnerable as the value of parameter alpha increases, while the similar feature cannot be observed in the case of random attack.